2016
DOI: 10.1002/ece3.2166
|View full text |Cite
|
Sign up to set email alerts
|

The Urban Heat Island and its spatial scale dependent impact on survival and development in butterflies of different thermal sensitivity

Abstract: Climate alteration is one of the most cited ecological consequences of urbanization. However, the magnitude of this impact is likely to vary with spatial scale. We investigated how this alteration affects the biological fitness of insects, which are especially sensitive to ambient conditions and well‐suited organisms to study urbanization‐related changes in phenotypic traits. We monitored temperature and relative air humidity in wooded sites characterized by different levels of urbanization in the surroundings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
90
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 61 publications
(78 reference statements)
5
90
1
Order By: Relevance
“…Non-significant pathways are given in dashed grey lines. These results are in line with recent results on community responses to urbanization in invertebrates (Kaiser et al, 2016;Piano et al, 2017) and suggest that the studied D. magna populations are quite well equipped to cope with the observed urban-driven warming of habitats in Flanders. (b) Proportional contribution of significant indirect (via size) and direct pathways to the estimated total effect of urbanization (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Non-significant pathways are given in dashed grey lines. These results are in line with recent results on community responses to urbanization in invertebrates (Kaiser et al, 2016;Piano et al, 2017) and suggest that the studied D. magna populations are quite well equipped to cope with the observed urban-driven warming of habitats in Flanders. (b) Proportional contribution of significant indirect (via size) and direct pathways to the estimated total effect of urbanization (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…(), the changes in temperature/humidity needed to observe changes in mesh width of the same magnitude as in our study are much greater than the average climate differences observed between urban and non‐urban sites in our study region (12°C against 1–2°C; Kaiser et al. ). This indicates that climate alone is unlikely to explain observed mesh width differences across urbanization gradients.…”
Section: Discussionmentioning
confidence: 40%
“…However, all environmental characteristics observed in this study either varied similarly at both scales (prey size, built‐up surfaces) or more prominently at the local scale (urban heat island effect; Kaiser et al. ). While other environmental effects cannot be ruled out, trait differences between landscapes also reflect dispersal effects.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations